1963
DOI: 10.1172/jci104860
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Production Rates in Normal Adults

Abstract: The investigation of clinical and physiological problems related to androgen production has been hampered by lack of an adequate measure of testosterone production. As one approach to this problem, Finkelstein, Forchielli, and Dorfman (1) developed a sensitive method for the measurement of free testosterone in plasma. The subsequent identification of testosterone in the urine (2) as the glucuronoside (3) provided a unique metabolite for the estimation of testosterone production rate by the isotope-dilution met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 22 publications
1
22
2
Order By: Relevance
“…The mean post hoc endogenous testosterone secretion rate at baseline in PK models for tT models was 12.5 mg/day. It is suggested that men produce between 4 and 11.8 mg of testosterone per day,23 which is slightly lower than our model estimate. However, there is wide variability in normal testosterone concentrations with ranges reported between 300 and 1,000 ng/dl,24 our model estimates of endogenous testosterone secretion rate are consistent with reported values and close to reported physiological values.…”
Section: Discussioncontrasting
confidence: 75%
“…The mean post hoc endogenous testosterone secretion rate at baseline in PK models for tT models was 12.5 mg/day. It is suggested that men produce between 4 and 11.8 mg of testosterone per day,23 which is slightly lower than our model estimate. However, there is wide variability in normal testosterone concentrations with ranges reported between 300 and 1,000 ng/dl,24 our model estimates of endogenous testosterone secretion rate are consistent with reported values and close to reported physiological values.…”
Section: Discussioncontrasting
confidence: 75%
“…Urinary "glucuronides" were hydrolyzed with /3-glucuronidase, and the liberated steroids were extracted with ether [21]. Urinary "sulfates" were hydrolyzed by solvolysis and extracted [21].…”
Section: Testosterone Conjugation Studymentioning
confidence: 99%
“…Urinary "glucuronides" were hydrolyzed with /3-glucuronidase, and the liberated steroids were extracted with ether [21]. Urinary "sulfates" were hydrolyzed by solvolysis and extracted [21]. Both extracts were counted, and then testosterone was isolated by thin layer chromatography and derivative formation [21].…”
Section: Testosterone Conjugation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Just as with other hormones such as hydrocortisone and aldosterone, the production rate of testosterone is determined from the cumulative specific activity of a urinary metabolite, i. e., testosterone glucuronide [16]. This urinary production rate (UPR) is approximately 7 mg/24 h for males and 1-2.5 mg/24 h for females [14,16,24,39]. For normal prepubertal children, only a few data are available.…”
Section: Introductionmentioning
confidence: 99%